Identification and validation of novel risk genes for intervertebral disc disorder by integrating large-scale multi-omics analyses and experimental studies - Zhang, Zhe; Chen, Yu; Wang, Qianjin; Li, Zheng; Dai, Bingyang; Dong, Cheng; Zhu, Zhengya (Frontiers in Medicine, 2025)
IntroductionAlthough genome-wide association studies (GWAS) have identified multiple genetic loci linked to intervertebral disc disorder (IDD), their functional characterization remains largely unelucidated. We aim to leverage an integrative analytical pipeline to identify novel IDD risk genes from genetic associations and experimentally validate their functional roles.MethodsWe integrated transcriptome-wide association studies (TWAS), proteome-wide association studies (PWAS), expression and protein quantitative trait loci (eQTL and pQTL) colocalization analyses to identify potential causal genes for IDD. Enrichment analysis, expression profiling, protein-protein interaction (PPI) network construction, and druggability evaluation were also performed for the prioritized causal candidates. Subsequently, human intervertebral disc (IVD) tissues spanning degeneration grades and an in vivo mouse IDD model were employed to functionally characterize candidate risk genes.ResultsIntegrative analysis of TWAS and PWAS with colocalization studies identified 104 genes and 10 proteins exhibiting causal associations with IDD. The identified genes/proteins were enriched in extracellular matrix organization, cellular senescence and collagen formation. Crucially, TMEM190, CILP2, and FOXO3 were demonstrated consistent evidence across TWAS, two independent PWAS datasets, and corresponding colocalization analyses, with CILP2 emerging as a potentially druggable target. Differential expression analysis revealed significant upregulated TMEM190 and CILP2, along with downregulated FOXO3 during IVD degeneration. These results were subsequently confirmed at protein levels in clinical specimens. Mouse model experiments further established that down-regulation of CILP2 alleviated IDD progression.DiscussionCollectively, this work provides an updated compendium of putative IDD risk genes and delineates pathogenic roles for TMEM190, CILP2, and FOXO3, providing a broad hint for further research on novel mechanism and therapeutic targets for IDD.